2009
DOI: 10.1093/ndt/gfp192
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-severe early-onset hyperuricaemia: a prognostic marker of long-term kidney transplant outcome

Abstract: Moderate-to-severe early-onset hyperuri- caemia may be a prognostic marker of the long-term graft outcome in RTRs, which needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
3
27
3
2
Order By: Relevance
“…But this is in contraindication to another study by Kanby M who found that uric acid level didn't differ significantly between renal transplant recipients receiving cyclosporine and non calcinurin inhibitors 36 . Also during the course of study 15% of normouricemic patients after 1 month of kidney transplant were converted at 6 months to patients having high uric acid level (data not shown).Our finding is consistent with adult kidney transplantation 37,38 and other solid organ transplantation 39,40,41 .…”
Section: Discussionsupporting
confidence: 84%
“…But this is in contraindication to another study by Kanby M who found that uric acid level didn't differ significantly between renal transplant recipients receiving cyclosporine and non calcinurin inhibitors 36 . Also during the course of study 15% of normouricemic patients after 1 month of kidney transplant were converted at 6 months to patients having high uric acid level (data not shown).Our finding is consistent with adult kidney transplantation 37,38 and other solid organ transplantation 39,40,41 .…”
Section: Discussionsupporting
confidence: 84%
“…Late-onset hyperuricemia mainly develops because of a gradual decrease in graft function, and it should therefore be regarded as a marker of chronic allograft nephropathy [13]. In contrast, early-onset hyperuricemia can develop without regard to reduced graft function and many previous reports suggest that it may play a predictive role in allograft outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that HUA is only a marker of graft dysfunction, [136][137][138][139] whereas some other studies suggest that UA is an independent risk factor for graft dysfunction. [140][141][142][143][144][145][146] Recently, Hart et al 147 reported that HUA correlated with tubular atrophy and interstitial fibrosis in chronic allograft nephropathy. Similar to the experimental findings, HUA in humans may exacerbate CsA nephrotoxicity.…”
Section: Hua and Renal Transplantationmentioning
confidence: 99%